The City, the Country, and Toronto’s Bloor Viaduct, 1897–1919 - Murnaghan, Ann (Urban History Review / Revue d'histoire urbaine, 2013)
There are certain structures in cities that exemplify the grandiose designs of the city builders at the turn of the twentieth century. The Prince Edward or Bloor Viaduct is one of these structures crossing Toronto’s key landform, the Don Valley, immortalized in Michael Ondaatje’s In the Skin of a Lion. Plans to build the bridge emerged as early as 1897, although the construction did not begin until 1913. The Bloor Viaduct can help us consider the progressive era by examining how discussions of nature/culture and country/city were incorporated into the discourses of its planning and construction. Technically, the bridge was an engineering feat spanning three valleys, making east-west travel in the growing city more efficient, improving the transportation of food and lumber. Symbolically, this monument highlighted the ability to overcome nature with a bridge and bring an aestheticized nature to the city. This contradiction between overcoming and improving access to nature is built into the bridge’s planning and construction history. By exploring the symbolic and material aspects of this bridge, the contradictions of nature in the process of nation building appear more striking.